GENDER, COGNITIVE STYLE, AND ITS RELATIONSHIP WITH CRITICAL THINKING: A LITERATURE REVIEW - Sukarma, I Ketut (Jurnal Ilmiah IKIP Mataram, 2019)
Critical thinking skills are cognitive processes carried out as guidelines for thinking using reasoning according to evidence, context, standards, methods, and conceptual structures by making concepts, implementing, synthesizing and or evaluating information obtained from observation, experience, reflection, thought, or communication as a basis for believing and taking action and focusing on deciding what to do. Gender is a different role in the social, mental, and level of thinking based on male and female sex which influences the cognitive style of students. Cognitive style is the tendency of individuals to consistently use preferred methods when organizing and processing information and experiences that are influenced by the ability to monitor and evaluate knowledge possessed both consciously and unconsciously. Students' critical thinking skills are closely related to gender and cognitive style. Gender plays an important role in shaping the character of students and cognitive styles that are closely related to the main indicators of students' critical thinking such as analysis, self-regulation, evaluation, the ability of students to defend opinions to make good decisions. The ability of critical thinking of students should be identified through the cognitive style of students.